2019
DOI: 10.1152/ajpendo.00140.2018
|View full text |Cite
|
Sign up to set email alerts
|

Multitissue analysis of exercise and metformin on doxorubicin-induced iron dysregulation

Abstract: Doxorubicin (DOX) is an effective chemotherapeutic treatment with lasting side effects in heart and skeletal muscle. DOX is known to bind with iron, contributing to oxidative damage resulting in cardiac and skeletal muscle toxicity. However, major cellular changes to iron regulation in response to DOX are poorly understood in liver, heart, and skeletal muscle. Additionally, two cotreatments, exercise (EX) and metformin (MET), were studied for their effectiveness in reducing DOX toxicity by ameliorating iron dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Ferritin is an iron storage form; it is one of the biomarkers of inflammation. In bacterial or viral infection, an increase in ferritin occurs due to ironreleasein the endoplasmic reticulum and to a decline in its transport capacity due to spleen and liver damage ( 9 ). Lactate dehydrogenase (LDH) is an enzyme involved in glycolysis, catalyzes pyruvate to lactate conversion and present in all tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Ferritin is an iron storage form; it is one of the biomarkers of inflammation. In bacterial or viral infection, an increase in ferritin occurs due to ironreleasein the endoplasmic reticulum and to a decline in its transport capacity due to spleen and liver damage ( 9 ). Lactate dehydrogenase (LDH) is an enzyme involved in glycolysis, catalyzes pyruvate to lactate conversion and present in all tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, preclinical studies have demonstrated that aerobic exercise training can modify DOX-induced hepatotoxicity and prevent DOX-induced maladaptations to the liver. Specifically, preconditioning protocols utilizing treadmill exercise ranging from 6 wk to 5 days before DOX administration provided valuable modifications to hepatocyte signaling (1,2,50,79,128). These studies demonstrate improvements in oxidative stress signaling, mitochondrial function, iron dysregulation, and insulin-like growth factor signaling and support the inclusion of exercise training as an advantageous therapy to preclude DOX hepatotoxicity (1,2,50,79,128).…”
Section: Livermentioning
confidence: 83%
“…Chemotherapy is a kind of common treatment for cancer, but both traditional drugs, such as doxorubicin, cisplatin or paclitaxel, and targeted drugs, like trastuzumab or immune checkpoint inhibitors, can cause a certain degree of cardiotoxicity. Taking doxorubicin as an example, current studies have shown that doxorubicin can cause iron overload in cardiomyocytes, further aggravate oxidative stress [10,11,12] , at the same time, cardiomyocytes metabolism disorder and structural change are contributed to myocardial cell apoptosis, necrosis and even increasing Gasdermin D sequentially leading to membrane dissolution [13,14] . However, the speci c mechanism of cardiotoxicity caused by targeted drugs has been on studying, but metabolism disorder, oxidative stress and in ammation are potential reasons.…”
Section: Discussionmentioning
confidence: 99%